«FUNDAMENTALS OF ACADEMIC WRITING» IN HIGHER EDUCATION INSTITUTIONS: AN INTERDISCIPLINARY APPROACH - Serebrianska, Irina (Educological discourse, 2021)
The article deals with the implementation of the discipline “Fundamentals of Academic Writing” in higher education institutions. The author represents her own experience of working on the course with students of different specialities, offers the main stages of training and approximate tasks. The discipline “Fundamentals of Academic Writing” is to form students’ academic culture, academic literacy, practical skills of oral and written language, necessary for successful learning and obtaining a future profession, and to develop critical thinking. Students learn to write professional and business texts of various types and give a critical assessment of information. They use a creative approach, library catalogues and websites. Both individual and teamwork in creating their micro-projects as a form of final control are encouraged. The interdisciplinary direction of the course is due to its content and structural elements: academic and scientific speech issues are closely intertwined with professional ones, forming the ability to express themselves competently within the speciality mastered by students, to create their professional texts. Integrated activities used in practice allow to develop various skills and abilities of future specialists: a study of educational and special terms, discussion of principles of academic integrity and related concepts (academic culture, academic ethics, academic writing, etc.), work with texts of different types, development of speech culture, writing resumes, cover letters, annotations, abstracts, essays and other documents essential for the further implementation of academic mobility of students and their successful participation in grant activities. The final work is in the form of presentation of the Code of Honor of the academic group developed by students. It is good feedback for the teacher about gained knowledge and skills. The interdisciplinary approach allows training modern specialists with good communicative competencies.